Berakhirnya Perjanjian Kerja Laut Karena Kecelakaan Kapal Tenggelam (Studi Kasus Putusan Nomor 84/PDT.SUS-PHI/2023/PN SBY) - Yanti, Helen; Wibawa, Risan; Saepudin, Wahyu (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The Maritime Employment Agreement (PKL) is the legal basis for the employment relationship between seafarers and maritime transport operators. One of the issues that often arises is the legal status of the PKL in the event of a maritime accident, particularly the sinking of a vessel. In this context, the question arises as to whether the PKL automatically terminates, and whether the operator remains obligated to pay the seafarers' entitlements, such as severance pay, wages, and compensation. This study aims to examine legal protection for seafarers in force majeure situations based on Article 27 of Government Regulation No. 7 of 2000, which states that employers remain obligated to pay severance pay equivalent to two months' final salary and other entitlements. This study highlights Decision Number 84/Pdt.Sus-PHI/2023/PN SBY, in which the heirs of a sailor sued the company for failing to fulfill employment rights, using a normative juridical method with a legislative approach and case studies. The focus is on analyzing legal norms related to seafarers' rights under force majeure conditions and reviewing relevant court decisions to evaluate the consistency of law enforcement. The analysis results indicate that the court ruled fairly by emphasizing that force majeure does not exempt employers from liability. However, there are still weaknesses in the implementation of seafarers' legal protection, particularly in terms of government outreach and oversight. Therefore, legal protection must be strengthened systematically to ensure that seafarers and their families receive genuine justice.